Tourism employment - "Riley, Michael" (New Delhi, 2006)
Tourism is a hard industry to 'see'- its diversity and fragmentation make it difficult for either analysis or synthesis to make holistic sense. Nevertheless, this book is an attempt to understand tourism employment in such a holistic way. Using ideas from: labour economics, work psychology and industrial sociology, the authors look at tourism employment in both its workplace context and its wider economic and social environment, and attempt to tell a coherent story. Both behavioural and economic perspectives are used to address questions that are salient to manpower planning, education planning and tourism management. The nature of jobs and mobility patterns lie at the heart of the book. By examining the diversity and commonality within occupations against the background of a dynamic labour market, the text develops themes that contribute to our understanding of the behaviour of workers and managers in the industry. The book begins with an analysis of key industry dimensions such as productivity, pay and occupational diversity. It then uses investigative techniques of manpower planning to show how behavioural patterns can helpfully contribute to macro level analysis. The final part of the book. looks at the consequences of such analysis for the planning function, human resource management and vocational education.
Keywords: Industrial tourism